2014
DOI: 10.1037/cou0000043
|View full text |Cite
|
Sign up to set email alerts
|

Revised and abbreviated forms of the Genderism and Transphobia Scale: Tools for assessing anti-trans* prejudice.

Abstract: Many studies of anti-trans prejudice have measured such attitudes using the Genderism and Transphobia Scale (GTS; Hill & Willoughby, 2005). The GTS is unique in assessing negative attitudes and propensity for violence toward trans people. The present research addressed previously observed limitations in the psychometric properties of data produced by the GTS, including inconsistencies in factor structure and subscale scoring across studies. Results across the present 2 studies (Ns = 314 and 250) yielded 2 refi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(116 citation statements)
references
References 44 publications
(127 reference statements)
6
98
0
2
Order By: Relevance
“…Prior research has relied on terminology that only partially encompasses the manifestations of negative reactions to transgender individuals. For example, existing terms like "transphobia" and "transprejudice" focus primarily on negative attitudes and emotions, particularly fear (Hill & Willoughby, 2005;John, Loewenstein, & Prelec, 2009;Tebbe, Moradi, & Ege, 2014;Winter et al, 2009). Of importance, these terms obscure other negative reactions, such as stereotyping, discriminatory behavior, and physical violence.…”
Section: Defining Gender Identity Biasmentioning
confidence: 99%
“…Prior research has relied on terminology that only partially encompasses the manifestations of negative reactions to transgender individuals. For example, existing terms like "transphobia" and "transprejudice" focus primarily on negative attitudes and emotions, particularly fear (Hill & Willoughby, 2005;John, Loewenstein, & Prelec, 2009;Tebbe, Moradi, & Ege, 2014;Winter et al, 2009). Of importance, these terms obscure other negative reactions, such as stereotyping, discriminatory behavior, and physical violence.…”
Section: Defining Gender Identity Biasmentioning
confidence: 99%
“…Higher scores on the GTSRSF Genderism/Transphobia scale indicate higher levels of antitrans attitudes. Tebbe et al, (2014) reported a .93 Cronbach's α for the Genderism/Transphobia subscale items, as well as evidence for convergent and discriminant validity. In the present study, Cronbach's α was .97 for the Genderism/Transphobia subscale, demonstrating strong internal consistency.…”
Section: Methodsmentioning
confidence: 95%
“…The GTSRSF (Tebbe et al, 2014) is a revision of the original Genderism and Transphobia Scale (Hill & Willoughby, 2005). The GTSRSF con tains two subscales (a) Genderism/Transphobia, an overall negative evaluation and negative emotions associated with gender nonconformity; and (b) Gender Bashing, which refers to the propensity for explicit harassment and/or assault toward trans individuals (Tebbe et al, 2014). Because the present study focused on more subtle and nonviolent forms of antitrans attitudes, the 5item GenderBashing subscale was not included in the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also controlled for previous contact with transgender people using three items adapted from Fingerhut () based on past research showing that intergroup contact is related to behaviors toward sexual minorities (e.g., Mereish & Poteat, ). Attitudes toward gender identity minorities using nine items from Tebbe, Moradi, and Ege's () transphobia measure and social desirability using Reynolds' () 12‐item measure were controlled as both may impact ratings of gender minorities in employment contexts (Pichler et al, ).…”
Section: Methodsmentioning
confidence: 99%